La radicalidad del mal banal - Marrades, Julián (Logos. Anales del Seminario de Metafísica, 2002)
‘Banality of evil’ was a concept introduced by Hannah Arendt in order to characterize a new form of wickedness embodied in people as Adolf Eichmann and others nazis criminals. Arendt thougt that this perverseness was very awey from the one of ‘radical evil’, a notion built by Kant and employed by Arendt herself in former works. This article seeks to point out that concepts of radical evil and banality of evil are closer than Arendt recognizes.